Evaluating client functioning in a harm reduction program in South Africa: insights from a tool derived from the International Classification of Functioning, Disability and Health - Janse van Rensburg, Michelle N. S.; Casteleijn, Daleen; Scheibe, Andrew (Frontiers in Rehabilitation Sciences, 2024)
South Africa faces the detrimental effects of problematic substance use. The Community Oriented Substance Use Program (COSUP) is a research-based, community-situated harm-reduction program. The International Classification of Functioning, Disability and Health (ICF) was used as the framework to develop a unique tool to determine the functioning of COSUP clients. The study was a quantitative descriptive, cross-sectional design, with data collected from COSUP sites during January 2023 using the COSUP Client Functioning Tool. Twenty-three Likert-scale structured closed questions about clients’ perceptions of their functioning and context were analyzed using descriptive statistics. Open-ended questions about COSUP services were thematically analyzed. Most COSUP clients are working-age African males, and many are unemployed. Clients seem to be coping well physically but need more mental health support. Pressing concerns for COSUP clients are feeling stressed and anxious, an inability to handle stress, poor use of free time, not getting support from others, and not having enough money to meet daily needs. Lack of energy and boredom are significant concerns, along with feelings of rejection and loneliness. Facilitating opportunities for sustaining livelihoods requires focus. Even so, there are those who have a sense of hope due to the positive impact of the program. Basing the COSUP Client Functioning Tool on the ICF framework provided a useful picture of the functioning of people who use/d drugs in their contexts. The COSUP Tool is helpful to guide interventions that are responsive to clients’ needs.